2003
DOI: 10.1002/clc.4960261304
|View full text |Cite
|
Sign up to set email alerts
|

New dimension of statin action on apoB atherogenicity

Abstract: Newer, more effective statins are powerful agents for reducing elevated levels of low‐density lipoprotein (LDL) cholesterol and thereby lowering the risk of coronary heart disease (CHD) and related adverse events. Although LDL remains the primary target of therapy for reducing CHD risk, increased interest is focusing on apolipoprotein B (apoB)‐containing lipoprotein subfractions—particularly very‐low‐density lipoprotein (VLDL), VLDL remnants, and intermediate‐density lipoproteins (IDL)—as secondary targets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Literature shows that lovastatin can lower apo B-100 protein level, 26 which is consistent with the results obtained for the MK group in this study. Furthermore, the experiment conducted in this study was the first time that MS and AK were observed to effectively reduce the expression of apo B-100 protein in the liver.…”
Section: A N U S C R I P Tsupporting
confidence: 94%
“…Literature shows that lovastatin can lower apo B-100 protein level, 26 which is consistent with the results obtained for the MK group in this study. Furthermore, the experiment conducted in this study was the first time that MS and AK were observed to effectively reduce the expression of apo B-100 protein in the liver.…”
Section: A N U S C R I P Tsupporting
confidence: 94%
“…The proteins that were found to be significantly differentially expressed in the 2 nd phase were then validated in the 3 rd phase in 506 samples (253 Cases and 253 Controls). Although Apo B was significantly down regulated in the 2 nd phase, it was not considered for the validation phase since it is known that statin decreases the levels of Apo B2526 and most of the CAD cases in our study were consuming statins. In fact, the lower expression of ApoB that was found in both the 1 st and the 2 nd phase lends credence to our results.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 The reduction in serum cholesterol level after treatment with EGEE may be due to improved elimination of LDL from plasma by mounting LDL-receptor activity. 23 X 100 X 100…”
Section: Resultsmentioning
confidence: 99%